Corporate marketing and service brands - Moving beyond the fast-moving consumer goods model. - McDonald, Malcolm; de Chernatony, Leslie; Harris, Fiona (Emerald, 2001)
Examines the issues associated with the creation and development of service brands in corporate branding. Initially considers the increasing importance of the services sector, the appropriateness of corporate versus individual branding and how service organisations have challenged the traditional approach to business. By analysing the success and failure of corporate branding in financial services, illustrates how thinking about service branding needs to change. Outlines the differences between product and service branding and considers how the fast-moving consumer goods (FMCG) approach to branding needs to be adjusted for the services sector. Particular emphasis is placed on the intangible nature of services and corporate branding and how problems linked to intangible offerings can be overcome. Concludes with an examination of the roles that employees and consumers play in the delivery and strengthening of the corporate service brands.